Room Temperature and Humidity Control System Using Arduino and Blynk - Purnomo, Beni; Sunardi, Sunardi (Peneliti Teknologi Teknik Indonesia, 2023)
The temperature and humidity of a room can be a problem that affects the comfort and health of its occupants. Issues such as excessively high or low temperatures and humidity levels can make it difficult for people to sleep and cause discomfort. Various solutions can be implemented, such as using IoT-based temperature and humidity monitoring systems, platform Blynk to optimize temperature and humidity control, and designing control circuits using actuators such as fans with relays. This control system uses the Blynk application to monitor and turn on and off the actuators in this study using a fan. Arduino Wemos D1 as the main processor, and for sensors, DHT22. Test method by placing the system in a room with an area of 3 x 3 m. The results of the test with the fastest average time were in the morning with a time of 10 minutes, 52 seconds. The longest average time was obtained during the day, with a test time of 14 minutes, 38 seconds. The difference in error between the system and the comparison is the highest at a temperature of 2.71% and at a humidity of 33.5%.